(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study delves into the concept of Green Human Resource Management (HRM) and its pivotal role in addressing Sustainable Development Goal (SDG) 13, focused on climate action. The research investigates the integration of environmental sustainability principles within HR practices to foster organizational resilience and contribute to mitigating climate change impacts. Drawing on a synthesis of contemporary literature, this study examines how HRM strategies, such as recruitment, training, performance management, and employee engagement, can be reshaped to incorporate environmental consciousness. It explores the potential of HR initiatives to nurture a culture of sustainability, instilling eco-friendly behaviours and fostering innovation in reducing carbon footprints. The study aims to highlight the importance of HRM as a catalyst for sustainable development, emphasizing its capacity to align individual and organizational goals with environmental objectives. Through this exploration, it endeavours to offer insights and recommendations for businesses to embrace Green HRM practices, thus playing a vital role in achieving SDG 13 and advancing the global sustainability agenda.